Дослідження соціальних та екологічних втрат від війни в Україні - Латишева, О.В.; Ровенська, В.В.; Смирнова, І.І.; Міхєєв, О.Ю. (Економічний вісник Донбасу, 2022)
У статті проаналізовано соціальні, економічні та екологічні наслідки бойових дій в Україні. Встановлено, що прояв жахливих наслідків російсько-української війни в Україні насамперед полягає в значних прямих людських втратах, колосальних руйнуваннях, подальшій небезпеці постійних обстрілів, погіршенні якості життя населення і вимушеній міграції. Встановлено, як вимушена міграція українців в більш безпечні міста впливає на національну економіку та економіку інших країн. Проаналізовано динаміку рівня якості життя та встановлено чинники впливу на індикатори цього критерію. Проаналізовано зміни соціальних показників, оцінена динаміка параметрів забруднення довкілля і з'ясовано характер та кількість екологічних злочинів від бойових дій в Україні. Доведено, що актуальність проблеми подолання негативних кризових явищ вимагає об’єднання зусиль міжнародної спільноти, урядів країн, бізнесу та громадян, фахівців різних галузей економіки, волонтерів, активістів, «лідерів думок», науковців тощо. Доказано, що вже зараз уряд країни приймає програми відбудови країни для зниження рівня соціально-економічних та екологічних ризиків. Проведено огляд прийнятих програм для зниження існуючих ризиків в Україні для подолання наслідків російсько-української війни у майбутньому. The article analyzes the social, economic and environmental consequences of hostilities in Ukraine. It has been established that the manifestation of the terrible consequences of the Russian-Ukrainian war in Ukraine primarily consists of significant direct human losses, colossal destruction, the further danger of constant shelling, deterioration of the quality of life of the population and forced migration. It is established how the forced migration of Ukrainians to safer cities affects the national economy and the economy of other countries. The dynamics of the level of quality of life were analyzed and the factors affecting the indicators of this criterion were determined. The changes in social indicators were analyzed, the dynamics of environmental pollution parameters were assessed, and the nature and number of environmental crimes from hostilities in Ukraine were clarified. It has been proven that the urgency of the problem of overcoming negative crisis phenomena requires the unification of the efforts of the international community, country governments, businesses and citizens, specialists in various branches of the economy, volunteers, activists, "opinion leaders", scientists, etc. It has been proven that the country's government is already adopting the country's reconstruction programs to reduce the level of socio-economic and environmental risks. A review of the adopted programs to reduce the existing risks in Ukraine to overcome the consequences of the Russian-Ukrainian war in the future was conducted.